2012
DOI: 10.1111/j.1556-6676.2012.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionality Dilemma: Patterns of Teacher Referrals to School Counselors for Disruptive Behavior

Abstract: Disproportionality plagues schools nationwide in special education placement, dropout, discipline referral, suspension, and expulsion rates. This study examined predictors of teacher referrals to school counselors for disruptive behavior in a sample of students selected from the Educational Longitudinal Study 2002 (National Center for Education Statistics, n.d.). Findings demonstrated that students’ race predicted English teacher referrals; students’ gender, previous disciplinary infractions, and teachers’ pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 49 publications
3
57
0
Order By: Relevance
“…For instance, in a review of secondary data from the National Education Longitudinal Study (NELS:88), researchers Adams, Benshoff, and Harrington (2007) found that teachers were more likely to contact the school counselor concerning behavioral issues when the student was male and African American. Moreover, a study that used the Educational Longitudinal Study (ELS:2002) that was conducted by Bryan, Vines, Griffin, and Moore-Thomas (2012), found that race was a predictor of disciplinarian referrals written by English teacher referrals. African American students in general and in particular African American and multiracial females were more likely to receive disciplinary referrals to the school counselor by their English teachers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a review of secondary data from the National Education Longitudinal Study (NELS:88), researchers Adams, Benshoff, and Harrington (2007) found that teachers were more likely to contact the school counselor concerning behavioral issues when the student was male and African American. Moreover, a study that used the Educational Longitudinal Study (ELS:2002) that was conducted by Bryan, Vines, Griffin, and Moore-Thomas (2012), found that race was a predictor of disciplinarian referrals written by English teacher referrals. African American students in general and in particular African American and multiracial females were more likely to receive disciplinary referrals to the school counselor by their English teachers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are school disciplinary (Gregory, Skiba, & Noguera, 2010;Shirley & Cornell, 2011), mental health (Miller & Taylor, 2012;Saluja et al, 2004;Sen, 2004) and socioeconomic (DeNavas-Walt & Proctor, 2014) disparities across different races/ethnicities in America. In the United States, African American, Latino, and Native American students are more often targets of a wide range of sanctions in schools including expulsion (KewelRamani, Gilbertson, Fox, & Provasnik, 2007), counselor referrals (Bryan, Day-Vines, Griffin, & Moore-Thomas, 2012), office discipline referrals (Skiba, Michael, Nardo, & Peterson, 2002), and suspension (Raffaele Mendez, Knoff, & Ferron, 2002;Raffaele Mendez & Knoff, 2003).…”
mentioning
confidence: 99%
“…Specifically, students’ gender was a predictor of both English and Math teacher referrals, whereas race was a predictor of only English teacher referrals. For example, it was found that black and multiracial females were more likely to receive disciplinary referrals to the school counsellor by their English teachers (Bryan, Day‐Vines, Griffin & Moore‐Thomas, ). Thus, we suggest that future research will examine the teachers’ specific consultations with educational counsellors regarding the students’ gender, their characteristics (IQ), or their personality (self esteem), in the specific context and other context, such as the Jewish society.…”
Section: Discussionmentioning
confidence: 99%